Participation Dynamics of Voters Using ID Card in Local Elections: A Case Study of the 2015 Local Election in South Sulawesi - Andi Ahmad Yani; Andi Yudha Yunus; Muhammad Iqbal Latief (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2017)
The number of voters is an essential element in the legitimacy of a democratic regime. There are various factors that may influence voter turnout in elections; among other factors particularly is electoral management in voter’s registration. The problem of voters' data has always been a scourge in every general or local election due to poor population data management in Indonesia. Hence, the General Elections Commission (KPU) responded to this issue with a number of policies to increase the number of voter participation in all elections, especially for those who have not been registered properly. The Commission made a specific regulation to allow voters who were not registered in the voter lists (DPS) to use their ID card (KTP) or other legal documents in voting. This study used qualitative methods in five regions in the South Sulawesi Province that conducted the 2015 local election. This study explores the dynamics of voters using ID card or other legal documents by identifying their reasons and characteristics in using KTP as well as examining the responses of the local election institutions regarding this policy. This condition tends to apply to countries in the transitional period of democracy where the electoral administration system has not been properly regulated. The causes include the failure of administrative systems of management and population data collection with e-KTP card system in Indonesia.